A Borneo Journey into Death : Berawan Eschatology from Its Rituals - Metcalf, Peter (SYMBOL AND CULTURE, 2017)
The unusual and symbolically complex funerary rites of the Berawan of central Borneo are here analyzed in the first such full-length study based on modern ethnographic research. Metcalf demonstrates how the ritual sand social organization of death serve as a crucial point of entry into the cosmology of a non-Western culture.